Cirques glaciaires et dispositif étagé dans les Macgillycuddy's reeks (comté de Kerry, Irlande) - Francis Huguet (Physio-Géo)
Remarkable glacial cirques were carved in Macgillycuddy's mountains (Co Kerry, Ireland) during the Quaternary cold periods. A morphometric study of thirty cirques west and south-west of Killarney and the reconstruction of the main features of the preglacial relief showed that climatic conditions alone cannot account for the location and size of the cirques. The field study confirms the existence in the area of stepped landforms, with the remnants of four stepped denudation surfaces, even if their dating and interpretation are still hypothetical. Most cirques abut against the breaks of slope separating the monadnocks from the upper surface or two successive stepped surfaces. Preglacial landforms, namely erosion scarps and stepped landforms favoured the accumulation of snow and ice and played an important part in the location and carving of the cirques.